Estudo das colocações de base verbal no livro Manuscritos baianos dos séculos XVIII ao XX: Autos de defloramento - Santos, Claudice Ferreira (2021)
The present thesis is the result of the study of Phraseological Units, exclusively, of the verbal basis, in the book: Bahian manuscripts from the 18th to the 20th centuries: Defloration records. In the book there is a semiplomatic edition of six deforestation records, under the organization of adviser professor Rita de Cássia Ribeiro de Queiroz. This dissertation includes the description of the corpus, the use of the computational tool AntConc, used for the survey and selection of UFs, and the glossary with the Phraseological Units of the specialized language contained in the corpus. The selection and collection of these elements were carried out with the help of phraseographic forms, which also contributed to the structural organization of the glossary. Based on the search and in possession of the data, we structured and organized a glossary of the Phraseological Units, supported by the set of information about a given lexeme, that is, the microstructure analyzed for the entries. In order for the study of the lexicon and related sciences we took: Preti (2003), Biderman (1981) (2001), Oliveira and Isquerdo (1998), Orsi (2012), Barreto (2014) and Almeida (2012); For the general taxonomy of Phraseological Units we look at the postulates of Blais (1993), Bevilacqua (1996), Corpas Pastor (1996), Welker (2004), Tagnin (2011), Monteiro Platin (2014) and Ortiz Alvarez (2011); regarding the Phraseological Units of the specialty language: Blais (1993), Pavel (1993a) (1993b) and Gouadec (1994); for the elaboration of the glossary of the Phraseological Units of the specialized language: Welker (2004), Finatto (2004), Krieger (2006), Pontes (2009) and Ximenes (2009) (2013).